ASI EKSKLUSIF DAN FAKTOR YANG MEMPENGARUHINYA : REVIEW - Sasube, Laurensi; Luntungan, Aldian H (Lasalle Health Journal, 2023)
Introduction: Exclusive breastfeeding is one way to reduce maternal and infant mortality in addition to producing quality human resources in the future. The best way to provide nutrition for babies is to fulfill the nutrition they need through exclusive breastfeeding them for 6 months followed by complementary feeding for up to 2 years in accordance with the Decree of the Minister of Health of the Republic of Indonesia. Breast milk is known for its advantages, but there is a tendency for mothers not to breastfeed their babies due to various factors. Objective: The purpose of this review is to examine the factors that influence exclusive breastfeeding in infants. Method: The literature review method. Result: The results obtained indicate that there are factors that influence exclusive breastfeeding to infants, including the level of knowledge and mother’s occupation, breastfeeding facilities in the office where the mother works and family support. Conclusions: Maternal factors, family, supporting facilities influence exclusive breastfeeding in infants.